(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2025)
This paper asks a key existential question: how, as existential practitioners, do we be ’in the room’ with suffering? It is a question that reverberates through all time, from the story of Job through all the world’s wars and, more recently, in the worldwide pandemic. Supporting nurses in a so-called ’safe’ room on a COVID ward, it arose for me in a new and more urgent way. I found myself turning to the writings of the French philosopher, Simone Weil (1909-1943) who sought to understand this most perplexing and distressing question.